Development of Critical Literacy Through Pancasila and Civic Education for Generation Z - Eka Rahma Salsabila; Febi Febriyan; Cindy Kartika; Taslim Batubara (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
The rapid flow of information in the digital age underscores the urgent need for critical literacy, particularly among Generation Z, to navigate, evaluate, and respond to diverse perspectives with discernment and responsibility. This study investigates the potential of Pancasila and Civic Education (PPKn) as a medium to cultivate critical literacy by embedding its values into educational practices. It examines the challenges educators face in integrating critical literacy into the PPKn curriculum and evaluates its impact on students' critical thinking skills. Utilizing a mixed-methods approach, the research incorporates qualitative interviews with educators and quantitative surveys of high school students to measure changes in their analytical and evaluative capacities. Findings indicate a notable enhancement in students’ ability to critically engage with socio-political issues, aligning their responses with the principles of Pancasila. The study also highlights the urgent need for innovative teaching methodologies and digital tools to optimize critical literacy outcomes. Ultimately, the research concludes that embedding critical literacy into Pancasila and Civic Education offers a transformative model for equipping Generation Z to become informed and responsible citizens. It emphasizes the importance of prioritizing critical literacy in curriculum development, ensuring it aligns with national values and addresses global challenges.